Principle of Consent in the Protection of Medical Personnel’s Personal Data: Implications and Consequences - Enrile Febriansyah, Juan Ponce; Kurnia, Ida (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2025)
Ideally, the principle of consent serves as the ethical and legal foundation for managing the personal data of medical personnel to ensure that every sensitive piece of information is processed transparently and securely. However, practical realities reveal weak compliance, limited awareness of data rights, and the rapid development of health technologies that are not yet balanced with adequate regulation. These conditions give rise to various legal issues, including data breaches and misuse of information that may harm medical personnel both personally and professionally. This study aims to analyze the position of the consent principle as one of the key pillars of personal data protection for medical personnel, while also outlining the implications and legal consequences of its implementation within the context of modern healthcare services. The methodology used in this study is categorized as qualitative library research, employing a normative legal approach explained through descriptive-analytical analysis. The findings indicate that the fulfillment of the consent principle has not been fully effective and still requires regulatory strengthening, enhanced data literacy, and consistent law enforcement to safeguard the integrity and security of medical personnel data.